Design of a Semi-Automatic Machine to Improve Garlic Processing for the Optimization of Procedures (Cutting, Shelling and Peeling) in Agricultural Areas - Llanco Guardia, Leonel Alvaro (2024)
This research presents the design of an automatic machine for post-harvest garlic processing, integrating 3 fundamental processes: garlic stalk cutting, garlic shelling and finally garlic peeling, in order to optimize production, improve quality and reduce costs. The development of the research is confined to farmers in the regions of Peru, contemplating the optimization and automation of 3 garlic processes, in order to allow a faster processing and relieve the farmer's workload. The initial part of the design is the cutting of garlic stalks, followed by the shelling of garlic cloves and then the peeling process, the processes have a system of vacuuming of waste and residues to obtain better product quality. The design is validated through previous research and with mechanical and electronic design software, concluding a significant improvement of 9.15% and 96% in the efficiency and quality of the product, cost reduction, production benefits and profitability in the processing of garlic and reducing the workload of the personnel.